Iraqi EFL teachers’ perception towards Google Classroom - Raed Latif Ugla; Mohammed Najim Abdullah (International Journal of Evaluation and Research in Education (IJERE), 2022)
Nowadays, information technology (IT) based educational applications (Moodle, Google Classroom, and Zoom) are available for both teachers and students. This study aimed to identify Iraqi English as a foreign language (EFL) teachers’ perception towards using Google Classroom at the university level. A qualitative research design (case study) was employed in this study. The researcher asked six Iraqi EFL teachers as volunteers to participate in this study. Those participants are working at different Iraqi universities. A semi-structured interview was used to get the data from those participants. Six phases of analysis were adopted to analyze the elicited data. The results revealed that Google Classroom is very important in EFL teaching and learning at tertiary level. This application has many advantages in teaching EFL students such as it enables students to find the lectures whenever they need them, encourages students to participate, speak, and comment freely and effectively without hesitations especially those who have some psychological problems like shyness. On the other hand, it has many disadvantages too such as it focuses on listening, writing, and watching skills and ignores the direct interaction between teachers and students, which could take place in the normal classes.